2018
DOI: 10.1111/pedi.12676
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control of type 1 diabetes in youth with autism spectrum disorder: A multicenter Diabetes-Patienten-Verlaufsdokumentation analysis based on 61 749 patients up to 20 years of age

Abstract: Metabolic control was similar in the T1D-ASD group compared to T1D-non ASD despite their comorbidity. Awareness of ASD remains important in T1D treatment, as both conditions require long-term multi-disciplinary medical follow-up for optimal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Interestingly, our data show a male to female ratio of 7.4:1 in participants in the T1DX compared with 4:1 in the general US population for ASD diagnosis [3,8]. The DPV data showed a 5.8:1 ratio of males to females in youth with ASD and Type 1 diabetes compared with a 2-3:1 ratio of males to females in the general German population with ASD [20,23]. Despite difficulties with social communication, the data from both the T1DX and DPV studies demonstrated no difference in diabetic ketoacidosis at presentation and during treatment, as well as no differences in severe hypoglycaemia events.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…Interestingly, our data show a male to female ratio of 7.4:1 in participants in the T1DX compared with 4:1 in the general US population for ASD diagnosis [3,8]. The DPV data showed a 5.8:1 ratio of males to females in youth with ASD and Type 1 diabetes compared with a 2-3:1 ratio of males to females in the general German population with ASD [20,23]. Despite difficulties with social communication, the data from both the T1DX and DPV studies demonstrated no difference in diabetic ketoacidosis at presentation and during treatment, as well as no differences in severe hypoglycaemia events.…”
Section: Discussionmentioning
confidence: 45%
“…Interestingly, our data show a male to female ratio of 7.4:1 in participants in the T1DX compared with 4:1 in the general US population for ASD diagnosis . The DPV data showed a 5.8:1 ratio of males to females in youth with ASD and Type 1 diabetes compared with a 2–3:1 ratio of males to females in the general German population with ASD .…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Prevalence of ASD: The prevalence of ASD in the Colorado pediatric population with T1D (1.16%) was similar to the prevalence of ASD in those with T1D in Ontario (0.9%), but higher than the prevalence of ASD in Ontario's general population (0.7%) and higher than the ASD prevalence in T1D in other countries, such as, Finland (0.14%), and Italy (0.72%) . Recently, the German/Austrian diabetes patient follow‐up registry, Diabetes‐Patienten‐Verlaufsdokumentation (DPV), reported the prevalence of comorbid ASD in T1D aged <20 years as 0.24%, but the prevalence of ASD in the general population was not provided . Differences in prevalence rates across the world may be because of differences in diagnostic criteria or in “diagnostic awareness” between countries.…”
Section: Discussionmentioning
confidence: 77%